(untitled) (Fiep Bulletin - online, 2014)
The present study it has the purpose to stand out one of the practicing pathologies that more to attack of Physical Exercises in the environment of the academies, the Vigorexia. For in such a way, we will be raising aspects concerning the necessity of opportunity a quarrel on this pathology and the understanding on the part of the professionals of Physical Education who if insert in this environment (academy), presenting subsidies that they will be able to make possible an interrelation between the Physical Education and other areas, emphasizing the health, the quality of life and the aesthetic one, value this that the society already assimilated as being part of its objectives in the search of an organized Physical Activity constant.